Comparison of Diagnostic Laparoscopy and Exploratory Laparotomy in the Management of Patients with Penetrating Abdominal Trauma - M Shams (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Patients with penetrating abdominal trauma can be treated with invasive procedures such as laparotomy and less invasive procedures such as laparoscopy. Since the management of patients with penetrating abdominal trauma based on non-invasive methods is more important, the present study was performed to compare laparoscopic and laparotomy methods to evaluate the surgical outcomes, complications and costs of patients with penetrating abdominal trauma. METHODS: In this retrospective study, the records of all patients with penetrating abdominal trauma and stable hemodynamics referred to Kowsar Hospital in Sanandaj during one year were reviewed. Patients' information including demographic characteristics, rate of laparotomy or laparoscopy surgery, time of operation, surgical wound infection, incidence of ileus, patients' pain intensity, length of hospital stay and hospital costs were collected and reviewed based on patients' records. FINDINGS: In this study, the medical records of 40 patients were reviewed. The average pain intensity in the laparoscopy group was 2.03±0.69 and in the laparotomy group was 6.77±1.95. Postoperative ileus was seen in 3 patients (16.66%) who underwent laparoscopy and 17 patients (77.2%) who underwent laparotomy. The average number of hospitalization days in the laparoscopy group was 1.38±0.61 days and in the laparotomy group was 5.73±1.78 days. The average cost of surgery in laparoscopic surgery was equal to 532240 Rials and in laparotomy was 1365600 Rials (p=0.0001). CONCLUSION: According to the results of this study, it seems that the use of diagnostic laparoscopic method for the management and treatment of patients with penetrating abdominal trauma and stable hemodynamics, significantly reduces complications and minimizes costs and length of hospital stay.